2013
DOI: 10.1080/13549839.2013.810205
|View full text |Cite
|
Sign up to set email alerts
|

Utilising resident feedback to inform energy-saving interventions at the Barbican

Abstract: The introduction of the Green Deal provides evidence of the UK Government's commitment to improving the energy efficiency of our ageing and underperforming housing stock. However, the issue of what to do with those buildings which for reasons of historical or architectural significance do not lend themselves to conventional fabric interventions has not been addressed fully. A residents' survey was conducted at the Grade II listed Barbican Centre in London, to characterise levels of occupant comfort and satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The four papers seek theoretical grounding in two main families of literatures: evaluation studies (Chmutina et al 2014, Sherriff 2014, Behar 2014) and social practice studies (Higginson et al 2014). They are all at the intersection between these literatures and a concern with energy and the built environment.…”
Section: Theoretical and Methodological Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…The four papers seek theoretical grounding in two main families of literatures: evaluation studies (Chmutina et al 2014, Sherriff 2014, Behar 2014) and social practice studies (Higginson et al 2014). They are all at the intersection between these literatures and a concern with energy and the built environment.…”
Section: Theoretical and Methodological Contextmentioning
confidence: 99%
“…Following a similar line of enquiry, Higginson et al (2014) question the relationship between practice and the household time-shifting of energy demand in order to understand demand flexibility better. Behar's (2014) paper mainly draws on the building evaluation literature, more specifically building use studies (BUS) and post occupation evaluation (POE) studies which look at building (energy) use and performance. In order to respond to the main limitation of this literature -i.e.…”
Section: Theoretical and Methodological Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…One step forward was achieved in the study of residents' behaviours and perceptions in the case of the Barbican Centre in London -a Grade II-listed residential and cultural complex built during the 1960s and a typical example of Brutalist architecture. 13 A residents' survey was conducted to characterise levels of occupant comfort and satisfaction, identify any problems experienced by the residents, and explore possibilities to improve the energy performance of the estate without compromising its status as an iconic example of post-war architecture and planning. This study showed that overall levels of satisfaction and comfort were high but residents were dissatisfied with the limited heating control.…”
Section: Energy Effi Ciency and Heritage Values In 'Heritage Buildings'mentioning
confidence: 99%